Perceived feedback and school belonging: the mediating role of subjective well-being - Li, Xinyu; Kuo, Yi-Lung; Huggins, Thomas J. (Frontiers in Psychology, 2024)
Introduction This study examined the interplay between perceived feedback (PF), subjective wellbeing (SWB), and students’ sense of belonging to school (SBS). School belonging is a key factor for decisions regarding academic studies, and is usually impacted by PF. The current study explored whether SWB mediates the established relationship between PF and SBS. Method This was achieved by applying a mediation model to PISA 2018 data from 12,058 students in four areas of China. Results Perceived feedback positively affected students’ SBS (β = 0.26, p < 0.01); and that SWB partially mediated this relationship between PF and SBS (β = 0.47, p < 0.01). Discussion The findings of this study have the potential to contribute to the existing literature on educational psychology and well-being. By shedding light on the mediating role of SWB, the research offers practical implications for educators and policymakers seeking to enhance students’ school belonging and other implications for their academic success. Further research can contribute to this promising area, by focusing on subjective wellbeing and its impact on a range of decisions being made by students during a critical phase of their personal and academic development.